NUTRITION IN PREGNANT WOMEN AND NURSING MOTHERS. DETERMINATE AND UNDECIDED PROBLEMS - O.A. Matalygina (Вопросы современной педиатрии, 2008)
The modern state of a problem of nutrition in pregnant women and nursing mothers is discussed and the ways of correction of nutrition with specialized milk formulas and vitamin mineral complexes are described.Key words: pregnant, nursing mothers, nutrition, vitamin mineral complexes.